2021
DOI: 10.32665/jurmia.v1i1.191
|View full text |Cite
|
Sign up to set email alerts
|

Peran Pendidikan Kepramukaan sebagai Media Pembentukan Karakter Kepemimpinan Siswa Sekolah Dasar

Abstract: Mendalamkan karakter kepemimpinan pada kegiatan ekstrakulikuler pramuka yang dilakukan oleh Pembina pramuka SDN Medalem I dengan tujuan agar siswa SDN Medalem I benar-benar memiliki karakter kepemimpinan yang baik dan penuh rasa tanggungjawab. Selain itu penerapan karakter kepemimpinan siswa pada ekstrakulikuler pramuka di SDN Medalem I dilakukan sejak dini agar mampu menerapkannya dalam kehidupan sehari-hari dan yang akan datang. Tujuan dari penelitian ini adalah untuk mengetahui proses implementasi dan manfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Empirical research support can also be found in studies identifying the positive impact of scouting on the development of student characters. Some studies state that scouting activities can enhance students' sense of responsibility, courage, as well as cooperation and leadership skills (Hidayati, 2021;Rozi & Hasanah, 2021). Therefore, through the integration of leadership theories and relevant research findings, it can be explained that scout extracurricular activities at Darul Muttaqien Boarding School play a crucial role in shaping the leadership character of students.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical research support can also be found in studies identifying the positive impact of scouting on the development of student characters. Some studies state that scouting activities can enhance students' sense of responsibility, courage, as well as cooperation and leadership skills (Hidayati, 2021;Rozi & Hasanah, 2021). Therefore, through the integration of leadership theories and relevant research findings, it can be explained that scout extracurricular activities at Darul Muttaqien Boarding School play a crucial role in shaping the leadership character of students.…”
Section: Resultsmentioning
confidence: 99%
“…Proses dalam pelaksanaan SLC meliputi sosialisasi kepada semua pihak yang terlibat, menyusun portofolio, merencanakan dan mempersiapkan pelaksanaan konferensi, melaksanakan konferensi, dan refeksi dan evaluasi (Barnet et al, 2005, n.p). Peneliti sebelumnya menjabarkan peran masing-masing pihak yang terlibat dalam kaitan dengan langka-langkah SLC seperti pada tabel berikut (Hidayati, 2021).…”
Section: Student-led Conference (Slc)unclassified